French and Spanish queer film : audiences, communities and cultural exchange - Perriam, Chris; Waldron, Darren (Edinburgh University Press, 2016)
Examines how LGBT filmmaking in France and Spain moves across borders and finds new audiences. Advancing the current state of film audience research and of our knowledge of sexuality in transnational contexts, French and Spanish Queer Film analyses how French LGBTQ films are seen in Spain and Spanish ones in France. Studying films from various genres, the book examines their reception across four languages (Spanish, French, Catalan, English) and engages with participants across a range of digital and physical audience locations. With a particular focus on LGBTQ festivals and on issues relating to LGBTQ experience in both countries, Perriam and Waldron consider issues such as ageing, sense of community and isolation, and the representation of issues affecting trans people. Examining films that chronicle the local (in portraying national and sub-national identities) while also addressing foreign audiences, the book draws on a wide sample of individual responses through post-screening questionnaires and focus groups, as well as drawing on the work of professional film critics and on-line commentators. Key Features. The first internationally comparative and crosscutting study of LGBTQ film, with audience research at its core Examines LGBTQ festivals in France and Spain Looks at the cross-border impact of the auteur and big-name directors Extensively covers independent and documentary film production as well as commercially-pitched feature films